CURRENT PHYSICAL EDUCATION TECHNOLOGIES AS THE KEY TO SUCCESSFUL PROFESSIONAL TRAINING OF FUTURE PHYSICAL EDUCATION TEACHERS - Dmitriieva, Nikol (SWorld-Ger Conference proceedings, 2023)
The purpose of the article is to highlight the forms of introduction of quasi-professional activities in the process of professional training of future teachers of physical education with the aim of forming their readiness for innovative activities. The m